2003
DOI: 10.1023/a:1023081624133
|View full text |Cite
|
Sign up to set email alerts
|

The 17q23 Amplicon and Breast Cancer

Abstract: A novel region of amplification in breast tumors was recently identified on chromosome 17q23. Extensive mapping of the amplicon by Southern blotting and fluorescence in situ hybridization (FISH) in breast cancer cell lines determined that the amplicon can be up to 4 Mbp in size and may contain 50 genes. Copy number analysis at 50-75 kb resolution in breast cancer cell lines and breast tumors identified several independently amplified regions within the amplicon, suggesting that a number of genes are selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
95
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 45 publications
6
95
0
1
Order By: Relevance
“…Thus, it would be of interest to know whether a simultaneous It remains to be determined whether there is an oncogene within the 17q23 breast cancer amplicon whose overexpression could drive tumorigenesis in transgenic mice. The 17q23 amplification occurs fairly frequently (B18%) in primary human breast cancers (Kallioniemi et al, 1994;Sinclair et al, 2003) and there are three potential oncogenes, RPS6KB1, TBX-2 and WIP1, which have been identified within this genomic locus (Sinclair et al, 2003). However, overexpression of either WIP1, Tbx2 or both in MMTVtransgenic mice is not sufficient for tumor formation (present study and data not shown).…”
mentioning
confidence: 47%
See 1 more Smart Citation
“…Thus, it would be of interest to know whether a simultaneous It remains to be determined whether there is an oncogene within the 17q23 breast cancer amplicon whose overexpression could drive tumorigenesis in transgenic mice. The 17q23 amplification occurs fairly frequently (B18%) in primary human breast cancers (Kallioniemi et al, 1994;Sinclair et al, 2003) and there are three potential oncogenes, RPS6KB1, TBX-2 and WIP1, which have been identified within this genomic locus (Sinclair et al, 2003). However, overexpression of either WIP1, Tbx2 or both in MMTVtransgenic mice is not sufficient for tumor formation (present study and data not shown).…”
mentioning
confidence: 47%
“…The initial observation of regional gain at chromosome 17q22-23 using a comparative genomic hybridization (CGH) technique detected amplification in B18% of primary breast tumors (Kallioniemi et al, 1994), giving its name to the locus as the 17q23 breast cancer amplicon. Three potential oncogenes, RPS6KB1, TBX-2 and WIP1 have been found within this genomic locus at chromosome 17q22-23 (Sinclair et al, 2003). However, it remains uncertain whether any of these oncogenes can induce mammary gland tumors when overexpressed in mice.…”
mentioning
confidence: 99%
“…The overexpression of Wip1 is likely to be oncogenic given its antagonism of key proteins involved in maintaining genomic stability. Indeed, the Wip1 gene at human chromosome 17q23 is amplified in 15% of human breast cancers, and its overexpression is found in an aggressive subset of breast, prostate, ovarian and brain cancers of poor prognosis (Hirasawa et al, 2003;Saito-Ohara et al, 2003;Sinclair et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…PS6K is a ribosomal protein that is involved in the progression from the G1 to S phase of the cell cycle. It is rapidly activated in response to mitogenic stimuli, for example, growth factors, cytokines, and oncogene products (Grove et al, 1991;Lane et al, 1993;Chou et al, 1995;Grammer et al, 1996;Thomas et al, 1997;Couch et al, 1999;Barlund et al, 2000b;Wu et al, 2000;Latham et al, 2001;Monni et al, 2001;Andersen et al, 2002;Li et al, 2002;Sinclair et al, 2002;Sinclair et al, 2003).…”
mentioning
confidence: 99%